HUBUNGAN LAYANAN BIMBINGAN KELOMPOK DENGAN SELF ESTEEM SISWA DALAM BELAJAR DI SMP NEGERI 1 PARIAMAN - erlizawati (Institut Agama Islam Sumatera Barat, 2025)
This study aims to analyze the relationship between group guidance services and the enhancement of students' self-esteem at SMPN 1 Pariaman. Students' self-esteem can be identified through low learning motivation, inability to concentrate, tendency to isolate themselves, and avoidance of social interactions. Group guidance services are expected to play a role in improving students' self-esteem, which in turn can influence their learning processes. This research employs a quantitative approach with a population of 180 eighth-grade students and a sample of 64 students. The instrument used is a questionnaire with a Likert scale, along with data collection through interviews and documentation. Data analysis was conducted using SPSS version 20. The results of the Rank Spearman test indicate a significant relationship between variable X (group guidance services) and variable Y (self-esteem), with a significance value (2-tailed) of 0.182, which is less than 0.05, indicating a correlation. The obtained correlation coefficient is 0.169, suggesting a moderately strong relationship between the two variables. These findings emphasize the importance of group guidance services in enhancing students' self-esteem, which positively impacts their learning processes.